Annual total rainfall amount at Gobabeb, Namibia - Yue Li; Eugene Marais; Lixin Wang (PANGAEA, 2025)
A six-decade-long dataset of the monthly and annual rainfall amount from 1962 to 2023 at Gobabeb, Namibia was compiled based on literature-derived dataset, public-available meteorological observations, and our measurement records. Monthly rainfall data at Gobabeb from September 1962 to December 2002 is available at Henschel and Seely (2008, doi:10.1016/j.atmosres.2007.11.015), and daily rainfall data during 2003-2014 was recordedavailable at the Gobabeb - Namib Research Institute. The daily rainfall data from October 2014 to December 2023 is available via https://sasscalweathernet.org/w_datarequest_we.php?MIsoCode=NA&MMCS=0#StationAnchor.
In: Li, Y et al. (2025): Monthly and annual total of moisture from 1962 to 2023 at Gobabeb, Namibia [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.981208